Gastrointestinal calcium absorption and dietary calcium load: relationships with bone remodelling in vertebral osteoporosis. - Tellez, M; Arlot, M; Mawer, E; Diaz, A; Hesp, R; Hulme, P; Edouard, C; Green, JR; Meunier, P; Reeve, J (Springer-Verlag, 1995)
Patients with vertebral osteoporosis have a wide range of bone loss rates, bone remodelling rates and capacities for gastrointestinal (GI) calcium absorption. To test the hypothesis that variations in GI absorptive capacity determine rates of bone loss or remodelling, we have sought relationships between calcium absorption or vitamin D metabolite levels on the one hand and rates of cancellous and cortical bone loss (measured by serial quantitative computed tomography in the radius; n = 25) or indices of bone remodelling in tetracycline-prelabelled transiliac biopsies (n = 41) on the other, in a sequential untreated group. Calcium absorption (net and true) was measured in 18-day balances and by a two-isotope deconvolution method (fractional absorption and maximum absorption rate, MAR). There was no significant seasonal effect on any of these four measures of calcium absorption (variance ratio, F = 0.52-1.61, p > 0.1) or on 1,25-dihydroxyvitamin D levels (F = 0.13, p > 0.1; range 11-69 pg/ml), notwithstanding the expected seasonal effect on 25-hydroxyvitamin D levels (mean 18.7 ng/ml, zenith mid July, semi-amplitude 7.5 ng/ml; F = 6.82, p < 0.01). Neither this metabolite nor 1,25-dihydroxyvitamin D correlated with any index of calcium absorption (p > 0.1). No measure of calcium absorption (or intake) had a significant relationship with radial cortical or cancellous bone loss (p all > 0.1) but cancellous bone loss was associated with the rate of endogenous calcium excretion (r = 0.50, p < 0.05).(ABSTRACT TRUNCATED AT 250 WORDS)